25-Hydroxy-vitamin D3 level is a predictor to insulin resistance in patients with hepatitis C virus-induced liver cirrhosis - Abir Zakaria; Nagwa Ramadan; Naglaa El-Sayed; Amr Zahra (SpringerOpen, 2013)
Background There is an established relationship between liver disease and hepatogenous diabetes mellitus, and a growing evidence for the role of vitamin D deficiency in the pathogenesis of type 1 and type 2 diabetes mellitus. However, data on the impact of vitamin D serum level on insulin resistance among liver cirrhosis patients are lacking. Objectives of the studyThe primary objective of the current study was to investigate the relationship between vitamin D status and insulin resistance among hepatitis C virus (HCV)-induced liver cirrhosis patients using a homeostasis model for assessment of insulin resistance (HOMA-IR). The secondary Objectives were to assess the association between deterioration of liver function on the one hand and insulin resistance and vitamin D deficiency on the other. Participants and methodsFifty patients with biopsy-proved HCV-induced liver cirrhosis were enrolled in this cross-sectional study. Routine clinical, laboratory, and imaging workout was performed to assess the degree of liver decompensation using the model of end-stage liver disease (MELD) score and the Child-Turcotte-Pugh Score (CTPS). Serum level of 25-hydroxy-vitamin D3 [25(OH)D3] was estimated. Fasting plasma glucose and fasting insulin were also measured to calculate HOMA-IR as an indicator of insulin resistance. Patients were subclassified according to serum 25(OH)D3 levels into tertiles, according to the MELD score into three groups, and according to CTPS into Child A, B, and C. Results A significant inverse correlation was found between serum 25(OH)D3 level and insulin resistance as assessed by HOMA-IR, whether using one-by-one correlation (r=-0.976, P=0.000) or using 25(OH)D3 tertiles' correlation (r=-0.830, P=0.000). Linear multiple regression analysis determined low serum 25(OH)D3 level as an independent predictor for increase in HOMA-IR among HCV-induced liver cirrhosis patients. No significant association was identified between low serum 25(OH)D3 level and the severity of liver dysfunction as assessed by the MELD score or CTPS. Conclusion The present study showed that low serum 25(OH)D3 level was an independent predictor for insulin resistance among patients with HCV-induced liver cirrhosis.